THE ROLE OF MODIFIED CHOLECYSTECTOMY IN THE SURGICAL TREATMENT OF CHRONIC CALCULOUS CHOLECYSTITIS (World Bulletin of Public Health, 2025)
The authors analyzed the results of surgical treatment of 1929 patients with chronic calculous cholecystitis (CCC). The patients were divided into two groups: a comparison group (776 patients, 2016–2018) and a main group (1153 patients, 2019–2021). The comparison group included 75 patients with traditional cholecystectomy (TCE), 536 with laparoscopic cholecystectomy (LCE), and 165 with cholecystectomy through a miniaccess. The main group consisted of 76 patients with TCE, 715 with LCE, 362 with a modified minimally invasive access. The authors summarize that the modified method of cholecystectomy through a mini-access is a reliable alternative to laparoscopic cholecystectomy, especially in the presence of contraindications